Effects of Saccharomyces cerevisiae in broiler diets: 1. Performance and meat composition - Acuti, Gabriele; Forte, Claudio; Miraglia, Dino; Branciari, Raffaella; Ranucci, David; Trabalza-Marinucci, Massimo; Pacetti, Deborah; Balzano, Michele; Frega, Natale G. (Progress in Nutrition, 2014)
The effects of a dietary supplementation with inactivated Saccharomyces cerevisiae on broiler performance and meat chemical composition were evaluated. The experimental protocol involved 600 day-old chicks allocated in 4 pens of 150 subjects each. The four diets were based on a commercial feed used as a control (C) enriched with conjugated linoleic (CLA) and ω3 polyunsaturated (ω3 PUFA) fatty acids. For the constitution of the other three experimental feeds, 150 mg/kg of vitamin E (E), 1.5 g/kg of inactivated yeast (Sc), or an association of vitamin E and inactivated yeast at the same doses above mentioned (ScE) were added. The animals were slaughtered at 54 days of age when they had an average live weight of 2300 g.In vivo and post mortem performance was higher in the ScE group compared to the other experimental groups. The dietary treatment did not induce changes in meat composition. The vitamin E supplementation resulted in a greater accumulation of PUFA and CLA in meat, when compared to the other treatments. The lowest values of CLA in muscle samples were recorded in the Sc and ScE groups. The TBARs method showed a marked positive effect of vitamin E on meat oxidative stability, with lower values recorded in both E and ScE groups. Further studies are needed to understand the inactivated yeast mode of action on intestinal ecosystem and on meat under different storage conditions.